DYNAMICS AND STRUCTURE OF MAIN INDICATORS OF THE AMERICAN BANKING SYSTEM - A.S. Filipenko; O.V. Bazhenova; М.M. Korol; M.I. Stehnei (Фінансово-кредитна діяльність: проблеми теорії та практики, 2020)
Abstract. The driving force of any country with market economy is the banking sector, which, as banking crises have shown, is not perfect and therefore needs more detailed study. This article from the series «Analysis of main indicators of the Anglo-Saxon banking system» is devoted to the study of the dynamics of main indicators of the American banking system for the period from 2000 to 2019 inclusive. Over the last decade, the number of commercial banks has decreased, including the United States (USA) ones. Based on data from the Federal Deposit Insurance Corporation (FDIC) with the separation of main studied indicators of the banking system and their detailed analysis, it was found that the financial crisis of 2008—2009 negatively affected the assets and liabilities of commercial banks, the dynamics of their net profit and increased the amount of outstanding loans. It is substantiated that despite the increase in private sector loans in the US, the latter do not show a high debt burden. It was also found that evidence of the consolidation process is an increase in specific gravity of the Top 5 largest banks in the country in total US banking assets. In this research, an attempt to study the effect of crisis in 2008-2009 indicators characterizing assets and liabilities of commercial banks in the United States has been made. Thus, to do this hypothesis to testify relationship of crisis in 2008—2009 and indicators characterizing assets and liabilities of commercial banks in the United States have to be tested. On the basis of the investigation, the conclusion was drawn that the dynamics of the main indicators of the American banking system for the period under study shows a positive trend, except for the financial crisis of 2008—2009. The number of banks is constantly decreasing, which is explained not so much by their liquidation as by their mergers and acquisitions. During the financial crisis of 2008, banks operated only with a profit of 10.2 billion dollars, which is 59.8% less than the previous year 2007. This is the lowest annual income since 1989. However, the significant increase in revenues in 2018 can be explained by the changes in taxation. At the same time, the share of outstanding loans has been declining every year since 2009, which is the evidence of prudent credit policy.